Determinants of capital structure in Nepalese commercial banks - Timilsina, Lalit Prasad (International Research Journal of MMC, 2020)
This study examines the determinants of capital structure in Nepalese Commercial Banks. The study is based on secondary data of 16 commercial banks with 112 observations for the period 2011/12 to 2017/18. The total debt to total assets and total debt to total equity were selected as dependent variables while return on assets, bank size, assets tangibility, assets growth and liquidity are the independent variables. The data were collected from annual reports of concerned sample bank. The Pearson's correlation coefficients and regression models are estimated to test the significance and impact of bank specific factors on the capital structure of Nepalese commercial banks. The result shows that banks size and assets tangibility are positively correlated with total debt to total assets whereas return on assets, assets growth and liquidity are negatively correlated with total debt to total assets. Likewise return on assets, bank size, assets tangibility, assets growth and liquidity are negatively correlated with total debt to total equity. It indicates that higher assets growth, return on assets and liquidity lower would be the total debt to total assets and total debt to total equity. Likewise higher the bank size and assets tangibility higher would be the total debt to total assets. This study concludes that return on assets, bank size and assets tangibility are the most influencing factors and assets growth and liquidity are the least influencing factor affecting the capital structure of Nepalese commercial banks.